2022
DOI: 10.17586/2226-1494-2022-22-3-509-516
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic properties of Ag-AgBr nanostructures in ion-exchanged layers of bromide sodium-zinc-aluminosilicate glass matrix

Abstract: https://orcid.org/0000-0002-1341-067X Аннотация Предмет исследования. Исследованы фотокаталитические свойства наноструктур Ag-AgBr, сформированных методом низкотемпературного ионного обмена с последующей термообработкой в натриево-цинкалюмосиликатном стекле с бромом. Метод. Синтезировано стекло на основе матрицы Na 2 O-ZnO-Al 2 O 3 -SiO 2 , легированной оксидами сурьмы Sb 2 O 3 , церия CeО 2 и бромом. Методом ионного обмена на поверхности натриево-цинк-алюмосиликатного стекла сформирован слой, содержащий ионы … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
0
0
Order By: Relevance
“…Sayyed et al 11 observed that the radiation shielding effectiveness of borate glasses embedded with low amounts of CrO 3 , and high levels of Na 2 O can be improved by doping AgI. Marasanov et al 12 reported the formation of the Ag–AgBr nanostructures by using the low-temperature ion exchange method and followed heat treatment in bromide sodium–zinc–aluminosilicate glass. They observed that the presence of a photocatalyst with Ag–AgBr nanostructures in the surface layer of glass under ultraviolet irradiation leads to better photocatalytic properties and the samples can be applied in devices for the photocatalytic decomposition of water to produce hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…Sayyed et al 11 observed that the radiation shielding effectiveness of borate glasses embedded with low amounts of CrO 3 , and high levels of Na 2 O can be improved by doping AgI. Marasanov et al 12 reported the formation of the Ag–AgBr nanostructures by using the low-temperature ion exchange method and followed heat treatment in bromide sodium–zinc–aluminosilicate glass. They observed that the presence of a photocatalyst with Ag–AgBr nanostructures in the surface layer of glass under ultraviolet irradiation leads to better photocatalytic properties and the samples can be applied in devices for the photocatalytic decomposition of water to produce hydrogen.…”
Section: Introductionmentioning
confidence: 99%